Identification Of Serum Micro-Rnas Of Early Knee Osteoarthritis In A Cohort Of Saudi Patients - Yami, Saleh Awad Saleh Al; Aljhani, Emad Abdulhamid; Daghriri, Yahya Muhammad Hassan; Al-Baqami, Mansour Sattam Nasser; Mohammed, Samerah Abdulraheem; Albawardi, Bander Saleh; Alotaibi, Hamdan Ayad; Abdullah Abdul Rahman Al Qasim; Saud Sunaidah Sufair Aljuaid; Saif Mazen Badri Aljabri; Maysaa Mansour Alazmi (Migration Letters, 2023)
Background: Osteoarthritis (OA), is a prevalent low-grade inflammatory synovial joint disease characterized by progressive cartilage degradation and alteration of the entire joint. Knee OA (KOA) is the commonest form of OA. Osteoarthritis is the 4th leading cause of disability worldwide with no cure and therefore identifying persons with early OA of the knee (KOA), is important to retard progression of the disease process. Several proinflammatory cytokines and microRNAs (miRNAs) are involved in OA pathogenesis. Objective: The aim of the work was to investigate the serum miRNA-136 (miR-136) and miR- 155-5p expression profile, IL-8 and IL-17 levels in subjects with early KOA and to further evaluate and compare the expression profile of these miRNAs, and level of serum IL-8 and IL- 17 in subjects with early and severe KOA. Methods: Serum miR-136 and miR-155-5p expression profile in 40 patients with early KOA were compared to 40 age and sex matched healthy controls and 10 patients with severe KOA. Clinical, laboratory, and disease parameters were assessed. Serum and synovial fluid miRNAs were assessed by real-time polymerase chain reaction. Levels of IL-17 and IL-8 levels were determined by the enzyme linked immunosorbent assay test. Results: miR-155-5p in serum was significantly higher in early KOA patients compared to healthy controls and to patients with severe OA. S[1]ynovial miRNA-155-5p expression levels were significantly higher than serum miRNA-155-5p in severe KOA patients compared to early OA patients. When we compared the expression levels of miRNA-136 between cases and healthy controls, there was no statistical significant difference, p=0.413. Serum IL-8 levels were significantly higher in early OA patients compared to healthy controls. Conclusions: Serum miR-155-5p and IL-8 levels are potential useful biomarkers for the early detection of OA and in particular, early KOA.